2009
DOI: 10.1007/s00240-009-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Problem in analyzing cystine stones using FTIR spectroscopy

Abstract: Cystine stones are produced by an inherited disorder of the transport of amino acid cystine that results in excess of cystine in the urine (cystinuria). Cystine calculi in urinary tract present a significant problem in patients. We have recorded that cystine calculi are very uncommon in our region. Cystine crystals are unusually identified in the urinary deposits. The problem of recognizing cystine by FTIR as a component in mixture of stones is significant. The problem is compounded by the similarity of wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…[6] Such analytical studies, incorporating both nondestructive and destructive analytical methodologies, have been conducted worldwide, providing significant information on the formation and composition of gallbladder stones and helping physicians to take prophylactic measures for the patients. [2,3,5] Following the classification of gallbladder stones by Grunhage and Lammert, [5] there exist yellowcolored pure cholesterol stones, black pigment stones, and brown pigment stones, while Jayalakshmi et al [7] refer to three morphological classes: cholesterol, pigment, and mixed stones. Considering the above-mentioned categorization, this study focuses on characteristic bladder calculi with distinctive morphology and structure.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[6] Such analytical studies, incorporating both nondestructive and destructive analytical methodologies, have been conducted worldwide, providing significant information on the formation and composition of gallbladder stones and helping physicians to take prophylactic measures for the patients. [2,3,5] Following the classification of gallbladder stones by Grunhage and Lammert, [5] there exist yellowcolored pure cholesterol stones, black pigment stones, and brown pigment stones, while Jayalakshmi et al [7] refer to three morphological classes: cholesterol, pigment, and mixed stones. Considering the above-mentioned categorization, this study focuses on characteristic bladder calculi with distinctive morphology and structure.…”
mentioning
confidence: 98%
“…Urinary stones are generally composed of organic materials and inorganic crystals (mainly of calcium, phosphate, magnesium salts, oxalate, and=or uric acid). [1][2][3][4] Gallbladder stones form when the concentration of cholesterol or bilirubin exceeds the solubility in the bile salt and phospholipid-rich bile and may develop a single, often large stone or many smaller ones, even several thousands. [2,3,5] Human gallstones occur in a variety of shapes, sizes, and crystalline to amorphous structures and range in color from creamy white and yellow to black and brown.…”
mentioning
confidence: 99%
“…13 In addition, the prominent peaks of S, C, O, and Ca were observed by EDS for cystine calculi. 12 These findings, combined with the results from FT-IR, showed that the sample contained COM and cystine.…”
Section: Gao Et Almentioning
confidence: 83%
“…[10][11][12][13] For instance, SEM-energy dispersive X-ray spectroscopy (EDS) was used to analyze the chemical element distribution in the surface and interior layers of CaOx stones.…”
Section: Gao Et Almentioning
confidence: 99%
“…However, it is inadequate to analyze cystine in compounds with a mixture of calcium oxalate and uric acid because of the overlapping of characteristic absorption bands; this technique often requires the confirmation by some other complementary methods. When chemical analysis is used as a complementary technique with FTIR for cystine containing stone identification, surprisingly very low success rate (10%) was confirmed by scanning electron microscopy with energy‐dispersive X‐ray spectroscopy (SEM‐EDAX) . The confirmation with SEM‐EDAX resulting in an unanticipated cystine stone occurrence rate of 0.2% (3 out of 1300 stones), which is 5–10 times lower than the worldwide statistical data (1–2%).…”
Section: Discussionmentioning
confidence: 99%